Vegetal and Animal Food Proteins Have a Different Impact in the First Postprandial Hour of Impedance-pH Analysis in Patients with Heartburn - Irene Martinucci; Giada Guidi; Edoardo V. Savarino; Marzio Frazzoni; Salvatore Tolone; Leonardo Frazzoni; Lorenzo Fuccio; Lorenzo Bertani; Giorgia Bodini; Linda Ceccarelli; Vincenzo Savarino; Santino Marchi; et al. (Gastroenterology Research and Practice)
Background and Aims. By means of 24 h impedance-pH monitoring, we aimed to evaluate the effect of two different meals with a bromatological balanced composition: one with a prevailing component of animal proteins and the other with vegetable proteins. Patients and Methods. We enrolled 165 patients with heartburn and negative endoscopy, who underwent impedance-pH monitoring off therapy. Patients were allocated to receive a Mediterranean diet with a total caloric intake of about 1694 kcal, divided into two meals: one with a prevailing component of animal proteins and the other with vegetable proteins. We evaluated the total reflux number, acid exposure time (AET), and symptom-reflux association with impedance-pH analysis. Moreover, during the first postprandial hour (at lunch and dinner), we evaluated the total reflux number, number of acid and weakly acidic refluxes, AET, and presence of symptoms. Results. The male/female ratio was 80/85. Mean age was 51.9 ± 12.1 years. Impedance-pH analysis showed that 55/165 patients had pathological AET or a number of refluxes (nonerosive reflux disease (NERD)), 49/165 had normal AET and a number of refluxes but positive symptom-reflux association (hypersensitive esophagus (HE)), and 61/165 had normal AET and a number of refluxes with negative symptom-reflux association (functional heartburn (FH)). The overall first postprandial hour analysis showed a higher total reflux number, acid reflux number, and AET after the animal protein meal than after the vegetable protein meal. Moreover, more symptoms were reported after the animal protein meal. Similar results have been observed in the three different subcategories of patients (NERD, HE, and FH). Conclusions. Vegetable proteins are associated with a lower number of refluxes, particularly acid refluxes, and with a reduced number of symptoms during the first postprandial hour. This is a pilot study and future investigations are warranted to confirm these results.